2016
DOI: 10.1097/iae.0000000000001034
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Fundus Autofluorescence Defects in Neovascular Age-Related Macular Degeneration Subtypes

Abstract: Presence of peripapillary fundus autofluorescence defects in neovascular age-related macular degeneration maybe suggestive of polypoidal choroidal vasculopathy as a variant of neovascular age-related macular degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…4 Third, atrophy is proposed to arise non-specifically in response to the exudative process itself, with episodic leakage over time, mechanical damage secondary to vascular outgrowth and contraction (dramatically demonstrated via OCT-angiography 62 ), and concomitant inflammation and ischemia. 3 Newly recognized forms of severe photoreceptor degeneration, 40 the non-progressive nature of RPE change at the ELM descent herein described, and FAF signatures consistent with a floodplain 3, 9, 19, 23, 57, 59 (Figure 7) support this third model, as do recent analysis of fellow eyes to those treated with anti-VEGF agents. 24 …”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…4 Third, atrophy is proposed to arise non-specifically in response to the exudative process itself, with episodic leakage over time, mechanical damage secondary to vascular outgrowth and contraction (dramatically demonstrated via OCT-angiography 62 ), and concomitant inflammation and ischemia. 3 Newly recognized forms of severe photoreceptor degeneration, 40 the non-progressive nature of RPE change at the ELM descent herein described, and FAF signatures consistent with a floodplain 3, 9, 19, 23, 57, 59 (Figure 7) support this third model, as do recent analysis of fellow eyes to those treated with anti-VEGF agents. 24 …”
Section: Discussionsupporting
confidence: 56%
“…Third, areas of absent FAF are preceded by and surrounded by areas of an abnormally granular FAF 21, 57 , seen as pigmentary disturbances in color imaging that are also associated with poor vision. 4 Fourth, several published FAF images 3, 9, 19, 22, 23, 57, 59 include a band of relatively uniform hyperautofluorescence with smoothly contoured edges surrounding atrophic areas (Figure 7B). This pattern recalls the inferior-angling gravitational tracks that typify central serous retinopathy 60 and gives the impression of fluid having washed over the RPE, like a floodplain of exudation.…”
Section: Discussionmentioning
confidence: 98%
“…12 By learning patterns and features of GA from extensive image databases, AI models can apply this knowledge to new images for automated GA diagnosis. 13 However, while deep learning models employing FAF and OCT have shown remarkable performance in identifying GA when compared with CFP, their practicality and availability in various healthcare settings remain limited. [14][15][16] In contrast, CFP stands out as a more widespread, accessible and cost-effective technique for GA screening and monitoring.…”
Section: How This Study Might Affect Research Practice or Policymentioning
confidence: 99%
“…FAF abnormalities have been shown to be more common in patients with PCV than in patients with retinal angiomatous proliferation or typical neovascular AMD. [ 44 ] Studies have demonstrated that PCV lesions show distinct FAF patterns. In a study by Yamagishi et al ., polypoidal lesions were observed as having confluent hypoautofluorescence, and BVN as having granular hypoautofluorescence.…”
Section: Diagnosis Of Pcvmentioning
confidence: 99%